Funciones desempeñadas en el Banco de Crédito del Perú – BCP periodo 2007 – 2018 - More Pezantes, Edinson Rolando (2019)
The following professional proficiency report aims to determine the credit grant management of the SME sector in the Trujillo BCP office; The main problem that was detected was The BCP makes a very fast and non-thorough rating with the client providing immediate preapproval without being able to see in what state the client is really in the financial system. The meaning of the description of what was found will be reflected in the utility that the BCP will receive for the granting of SME loans. All the steps of the credit process in the BCP were detailed. The following main conclusion was reached that the small business banking executive is the person responsible for the credit process, its general function being to promote, analyze, evaluate and process the approval of customer credit applications, ensuring quality of the portfolio it manages. Therefore, it is concluded that the recovery of a credit depends largely on the correct execution of the credit process carried out by the credit counselor.